Processing temperature and sugar type affect the rate and the extent of proteolysis of a model soy protein isolate system - Salazar Villanea, Sergio (2020)
Processing of ingredients and diets using hydrothermal treatments can lead to negative effects on the nutritional value of proteins, depending on the processing conditions and the matrix of the ingredient or diet. The aim of this study was to evaluate the effects of processing temperature and sugar type on the extent and rate of protein hydrolysis using soy protein isolate as a model system. The experiment utilized a 3☓3 factorial design, with three repetitions per treatment, using autoclaving temperature (not autoclaved, 100 ◦C, 120 ◦C) and type of sugar (not added, glucose, xylose) as main factors, also evaluating the interaction between both. Limited formation of Maillard reaction products occurred in the absence of sugars, whilst the addition of xylose increased the formation of MRPs at all processing temperatures. Crosslinks between amino acids (lysinoalanine, lanthionine) occurred with increasing temperatures, with sugar addition being inhibiting. There was a significant interaction (P < 0.01) between the effects of processing temperature and type of sugar for nitrogen solubility, the extent and rate of proteolysis. The effect of autoclaving at 100◦C on the rate of protein hydrolysis of the samples without sugars added was as high as the additional effect of autoclaving after the addition of sugars. In contrast, the effect of autoclaving at 120◦C on the rate of protein hydrolysis was higher for the samples that contained sugars, compared to those that did not had sugars added. In conclusion, the effect of sugar addition on the extent and rate of proteolysis seems to be dependent on processing temperature, which might indicate different protein damage mechanisms limiting enzymatic protein hydrolysis.